Exploring the nexus of nature-interaction and human needs maturity - Abu Bakar, Aisyah (Malaysian Institute of Planners, 2023)
This paper empirically explored the relationship between Interaction with Nature [IN] with three concepts, namely under Human Interdependence [HI], Subjective Well-being [SWB], and Maslow’s Hierarchy of Needs [HON]. Research Questions: Does the fulfilment of human needs elevate IN? Is it possible for IN to increase despite unfulfilled needs, and if so, which human needs have a trivial impact on IN? Purpose: This paper aimed to examine the variations of IN in relation to the difficulty and convenience of fulfilling human needs. Approach: Mann-Whitney U Test was conducted to determine the mean variation of IN across the difficulty and convenience of fulfilling 24 human needs. Findings: The convenience with which 10 of the human needs could be met significantly increased IN. Meanwhile, IN did not differ significantly across the convenience and difficulty of meeting the other 12 human needs, signifying their unlikeliness to influence IN. Furthermore, an intriguing statistical result was observed where fulfilling five of the human needs and fostering IN developed along independent trajectories. Additionally, the difficulties in meeting two of the human needs, namely (i) clean water and (ii) artistic and cultural freedom, significantly elevated nature-interaction.